Informed consent in minor and intermediate pediatric elective surgery: results of an in-house questionnaire - Stefani, Bianca; Codrich, Daniela; Caputo, Maria Rita; Guida, Edoardo; Scarpa, Maria-Grazia; Boscarelli, Alessandro; Schleef, Jürgen (Frontiers in Surgery, 2023)
Background: The aim of this study was to evaluate the quality of our surgical informed consent and parents’/guardians’ late recall of surgical procedures and risks of elective day surgery after pre-operative interview with surgeons. Methods: All parents/guardians of patients <18 years of age undergoing minor and intermediate elective procedures from January 15th to September 1st, 2022, were prospectively enrolled in the study. Before discharge, parents/guardians were asked to complete an in-house questionnaire regarding the duration of the consent procedure, duration of the inter-view, quality of the informative handouts, and their ability to recall the type of disease, type of surgical procedure, and surgical risks. Results: One hundred and two questionnaires were returned. In all cases, informed consent was obtained between 24 and 72 hours prior to surgery. The following responses were collected: 98/102 (96%) parents/guardians reported that the duration of the consent process was adequate; 95/102 (93%) reported that the handouts were fully informative, and 7/102 (7%) reported that they were partially informative regarding explanation of the disease and surgical procedure; regarding complications, 93/102 (91%) perceived the handouts to be fully/partially informative, while 4/102 (4%) perceived the handouts to be poorly/non-informative, and 5/102 (5%) did not provide a response; 94/102 (92%) stated that they remembered the pathology, but only 87/94 (93%) recalled it correctly; 90/102 (88%) stated that they remembered the type of procedure, but only 76/90 (84%) recalled it correctly; and 53/102 (52%) stated that they remembered the surgical risks, but only 20/53 (38%) could recall more than one complication. Conclusions: Late recall of surgical complications by parents was poor despite the high perceived quality of the surgical risk handouts and medical interview. Implementation of expedient methods may improve overall comprehension and satisfaction of parents/guardians regarding the IC process. Further, more efforts should be made to develop standardized guidelines for an optimal IC process.